Preparation method of a nanocomposite material and its application in detecting tetracycline antibiotics
By using Au@ZnO/Pt nanocomposites to perform coordination reaction and catalytic oxidation reaction with tetracycline, the problem of expensive equipment and complex sample pretreatment in the existing technology is solved, and the rapid, efficient and sensitive Detection effect.
Patent Information
- Application Number
- CN202410679801.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-05-29
AI Technical Summary
The prior art requires expensive and complex equipment, cumbersome and time-consuming sample preprocessing procedures, and trained technicians to detect tetracycline antibiotics, limiting its application.
Au@ZnO/Pt nanocomposites are used as components of fluorescent probes or test strips, and the zinc ions in the nanocomposites undergo coordination reaction with tetracycline to produce specific fluorescence enhancement, and catalyzed through oxidase-like activity properties. TMB oxidizes, producing color changes to detect tetracycline.
It realizes fast, efficient, sensitive and easy-to-operate tetracycline detection, with extremely low detection limits, and can accurately detect tetracycline antibiotics without the need for expensive equipment and complex sample pretreatment.
Smart Images

Figure CN118650156B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano materials and analytical testing, and in particular to a nano composite material and a preparation method thereof and application in detecting tetracycline antibiotics. Background Art
[0002] Tetracycline (TC) is a class of broad-spectrum antibiotics produced by Streptomyces. It is widely used in medicine, food, environment and other fields due to its excellent antibacterial properties, low toxicity, low cost and easy oral absorption. However, the abuse of TC will lead to high levels of TC residues in environmental media such as soil and water. TC residues are important organic pollutants in water bodies. They are difficult to degrade and remain active in environmental water, thus having an adverse impact on the ecosystem. In addition, the abuse of TC will also lead to bacterial resistance, reduce drug efficacy, and produce other toxicity to the human body.
[0003] At present, many analytical methods have been reported to determine TC, mainly the following: high performance liquid chromatography, liquid chromatography tandem mass spectrometry, capillary electrophoresis, enzyme-linked immunosorbent assay, lateral flow detection, and thin layer chromatography. These technologies have high sensitivity and accuracy and have become routine methods for detecting TC, but most of the above methods require expensive and complex equipment, cumbersome and time-consuming sample pretreatment procedures, and trained technicians, which limits their application. With the increasing concern about environmental quality and public health, it is necessary to develop a rapid, efficient, sensitive, and easy-to-operate method for tetracycline detection. Summary of the invention
[0004] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a nanocomposite material. The second purpose of the present invention is to provide a method for preparing the above-mentioned nanocomposite material. The third purpose of the present invention is to provide the application of the above-mentioned nanocomposite material in detecting tetracycline antibiotics. The fourth purpose of the present invention is to provide a method for detecting the concentration of tetracycline antibiotics.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention provides a nanocomposite material. The nanocomposite material is a core-shell structure, wherein the shell layer is zinc oxide, the core is gold nanoparticles, and the shell layer is loaded with platinum nanoparticles.
[0007] Preferably, the particle size of the nanocomposite material is 100-400 nm.
[0008] Preferably, the molar ratio of zinc oxide, gold nanoparticles and platinum nanoparticles is 10:(0.5-2):(0.5-2).
[0009] The second aspect of the present invention provides a method for preparing the nanocomposite material according to the first aspect, comprising the following steps:
[0010] S1, adding a thiol small molecule to the gold nanoparticle solution to react and obtain a reactant 1;
[0011] S2, reacting the reactant 1 with a zinc source and hexamethylenetetramine to obtain a reactant 2;
[0012] S3, reacting the reactant 2 with a platinum source to obtain the nanocomposite material. Preferably, the calcium salt is selected from calcium chloride, calcium nitrate or a combination thereof.
[0013] Preferably, in step S1, the gold nanoparticles are prepared by the following steps: a gold source is reacted with a reducing agent to prepare the gold nanoparticles.
[0014] More preferably, the gold nanoparticles are prepared by the following steps: chloroauric acid and sodium citrate react in an aqueous solution to prepare the gold nanoparticles. Further preferably, the molar ratio of chloroauric acid to sodium citrate is 1:(5-15).
[0015] Preferably, in step S1, the thiol small molecule is selected from one or more of thioglycolic acid, thioglycolate, mercaptoethanol, thioethanol salt, mercaptoethanesulfonic acid and mercaptoethanesulfonate.
[0016] Preferably, step S1 further comprises: adding reactant 1 to a solution containing a stabilizer, wherein the stabilizer is selected from one or more of PVP, PVA, Tween-80, and sodium dodecylbenzene sulfonate.
[0017] Preferably, in step S2, the zinc source is selected from one or more of zinc acetate, zinc nitrate, zinc sulfate and zinc chloride.
[0018] Preferably, in step S3, the platinum source is selected from one or more of sodium chloroplatinite, potassium chloroplatinite, ammonium chloroplatinite, chloroplatinic acid, and sodium chloroplatinate.
[0019] Preferably, in step S1, the reaction temperature is 50-70° C., and the reaction time is 1-3 h.
[0020] Preferably, in step S3, the reaction temperature of the reaction is 15-40° C., and the reaction time is 8-16 h.
[0021] The third aspect of the present invention provides the use of the nanocomposite material described in the first aspect in detecting tetracycline antibiotics.
[0022] Preferably, the tetracycline antibiotic is tetracycline, chlortetracycline or oxytetracycline.
[0023] Preferably, the nanocomposite material is used in the preparation of a fluorescent probe or a test strip for detecting tetracycline antibiotics.
[0024] More preferably, the test strip comprises: a nanocomposite material, 3,3',5,5'-tetramethylbenzidine TMB, and a buffer solution with a pH of 4 to 6. Further preferably, the method for detecting tetracycline antibiotics using the test strip is: dripping a test solution onto the test strip, and if the test strip shows fluorescence enhancement and / or color change, it is detected that the test solution contains tetracycline antibiotics.
[0025] A fourth aspect of the present invention provides a method for detecting the concentration of tetracycline antibiotics, comprising the following steps:
[0026] 1) mixing the nanocomposite material described in the first aspect, 3,3',5,5'-tetramethylbenzidine, and a tetracycline antibiotic standard solution to obtain a mixed solution, detecting the fluorescence intensity and / or ultraviolet light absorbance of the mixed solution, and establishing a relevant working curve;
[0027] 2) The method in step 1) is used to detect the fluorescence intensity and / or ultraviolet light absorbance of the test solution containing tetracycline antibiotics, and the concentration of the tetracycline antibiotics in the test solution is calculated.
[0028] Preferably, the pH of the mixed solution is 3-6.
[0029] Preferably, the mixed solution also includes PBS buffer.
[0030] Preferably, the reaction time of the mixing reaction is 3-15 min.
[0031] Preferably, the detection range of the fluorescence intensity is 400-650 nm.
[0032] Preferably, the detection excitation wavelength of the fluorescence intensity is 385 nm.
[0033] Preferably, the detection range of the ultraviolet absorbance is 200-800 nm.
[0034] The beneficial effects of the present invention are:
[0035] The invention provides an Au@ZnO / Pt nanocomposite material, the structure of the composite material is spherical zinc oxide coated gold nanoparticles, platinum nanoparticles are attached to the surface of zinc oxide, the material surface is rough, the material has good thermal stability and oxidase-like catalytic performance, good water solubility and dispersibility, and is convenient for water phase detection. The composite material is used for tetracycline antibiotic detection and belongs to a fluorescence enhancement probe material. Compared with fluorescence quenching materials, it has better specific selection, anti-interference and higher sensitivity. Therefore, the Au@ZnO / Pt nanocomposite material is used to detect tetracycline antibiotics, which can achieve fast, efficient, sensitive and simple detection.
[0036] The zinc ions in the Au@ZnO / Pt nanocomposite of the present invention will coordinate with tetracycline to generate specific fluorescence enhancement, converting tetracycline with weak orange fluorescence into tetracycline with strong green fluorescence, and establishing a fluorescence analysis method for detecting tetracycline in a sample through the linear relationship between the generated strong green fluorescence product and its fluorescence intensity and the concentration of tetracycline, with an extremely low detection limit of 0.48 nmol / L. At the same time, during the reaction, the oxidase-like activity of the Au@ZnO / Pt nanocomposite can catalyze the oxidation of TMB into ox-TMB, and tetracycline will interact with ox-TMB, which will hinder this process and cause the color change of the solution. Therefore, a colorimetric analysis method for tetracycline can be established through the linear relationship between the absorbance of the solution and the concentration of tetracycline, which also has an extremely low detection limit of 0.434nmol / L. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The transmission electron microscope (TEM) morphology structure diagram of Au@ZnO / Pt nanocomposite;
[0038] Figure 2 This is the energy spectrum analysis (EDS) result diagram of Au@ZnO / Pt nanocomposite;
[0039] Figure 3 A comparison of the oxidase-like activities of Au@ZnO / Pt nanocomposites and other nanocomposites;
[0040] Figure 4 The photograph is taken under ultraviolet light after the test substance tetracycline solution of the present invention is dripped onto the test paper prepared from the Au@ZnO / Pt nanocomposite material;
[0041] Figure 5 The photograph is a photo taken under natural light after the test substance tetracycline solution of the present invention is dropped onto the test paper prepared from the Au@ZnO / Pt nanocomposite material;
[0042] Figure 6It is an intuitive enzymatic diagram of Au@ZnO / Pt nanocomposites and other nanocomposites;
[0043] Figure 7 The results of establishing the tetracycline fluorescence working curve in Application Example 1, wherein (a) is the fluorescence emission spectrum of Au@ZnO / Pt in response to tetracycline solutions of different concentrations, and (b) is a linear relationship diagram between fluorescence intensity and tetracycline concentration;
[0044] Figure 8 The results of establishing the tetracycline colorimetric working curve in Application Example 2, (a) is the UV-visible absorption spectrum of Au@ZnO / Pt in response to tetracycline solutions of different concentrations, (b) is the linear relationship between absorbance and tetracycline concentration;
[0045] Fig. 9 The results of selective detection of tetracycline by fluorescence analysis of Au@ZnO / Pt nanocomposites in Application Example 3;
[0046] Fig.10 This is the selective detection result of tetracycline using colorimetric analysis of Au@ZnO / Pt nanocomposites in Application Example 4. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.
[0048] The PBS buffer, TMB solution, tetracycline solution and interferor solution used in the examples and experimental analysis were prepared as follows:
[0049] 1) Preparation of 10 mmol / L PBS buffer: Weigh 0.0599 g of solid sodium dihydrogen phosphate using an analytical balance, add it to a small amount of ultrapure water to dilute, transfer it into a 50 mL volumetric flask, and add water to the mark to obtain solution A; weigh 0.1791 g of solid disodium hydrogen phosphate dodecahydrate using an analytical balance, add it to a small amount of ultrapure water to dilute, transfer it into a 50 mL volumetric flask, and add water to the mark to obtain solution B; according to the required pH value, mix solution A and solution B in different proportions.
[0050] 2) Preparation of 600 μmol / L TMB solution: Weigh 0.0144 g TMB powder solid using an analytical balance, add to a small amount of ultrapure water for dilution, transfer to a 100 mL volumetric flask, add water to the mark to obtain a 0.6 mmol / L TMB solution; dilute to other TMB solutions of different concentrations as needed.
[0051] 3) Preparation of 300 μmol / L tetracycline solution: Weigh 0.0133 g of tetracycline powder solid using an analytical balance, add it to a small amount of ultrapure water for dilution, transfer it into a 100 mL volumetric flask, add water to the scale to obtain a 300 μmol / L tetracycline solution; dilute it into other tetracycline solutions of different concentrations as needed.
[0052] 4) Preparation of 100 μmol / L solution of other interfering substances: Calculate and weigh the corresponding weight of 100 μmol / L of various types of interfering substances, dilute with a small amount of water, transfer to a 50 mL volumetric flask, and add water to the scale to obtain a 100 μmol / L solution of other interfering substances; dilute to other interfering substance solutions of different concentrations as needed.
[0053] Example 1
[0054] This embodiment provides an Au@ZnO / Pt nanocomposite material, and the preparation method thereof is as follows:
[0055] (1) Preparation of gold nanoparticle solution: Add 100 mL of water and 125 μL of 100 mmol / L chloroauric acid solution to a three-necked flask. Heat the mixed solution to 145 °C until boiling while stirring vigorously. Quickly add 5 mL of 25 mmol / L sodium citrate solution and heat at 140 °C for 20 minutes. Cool to room temperature and store in a refrigerator at 4 °C.
[0056] (2) Preparation of AuNPs-TGA-PVP solution: Add 100 mL of the gold nanoparticle solution prepared in step (1) and 500 μL of 3 mmol / L ethanolic thioglycolate solution into a flask. Heat the mixed solution to 60°C with vigorous stirring for 2 h. Cool the mixed solution to room temperature and wash it by centrifugation. Mix it evenly with 50 mL of 100 μmol / L aqueous polyvinyl pyrrolidone solution and store it at 4°C.
[0057] (3) Preparation of Au@ZnO solution: Add 50 mL of the AuNPs-TGA-PVP solution prepared in step (2), 1 mL of 250 mmol / L hexamethylenetetramine solution, and 1 mL of 250 mmol / L zinc acetate solution into a flask. Heat the mixed solution at 95 °C for 3 h under vigorous stirring. After cooling to room temperature, wash the solution by centrifugation, disperse it back into water, and store it at 4 °C.
[0058] (4) Preparation of Au@ZnO / Pt nanocomposites: Take 15 mL of the Au@ZnO solution prepared in step 3 and add it into a flask. Add 250 μL of 100 mmol / L chloroplatinic acid under vigorous stirring and react at room temperature for 12 h to obtain Au@ZnO / Pt nanocomposites, which were then stored in a refrigerator at 4 °C.
[0059] The structure of the Au@ZnO / Pt nanocomposite material prepared in this example is spherical zinc oxide coated gold nanoparticles, platinum nanoparticles attached to the surface of zinc oxide, and the surface of the material is rough. The transmission electron microscopy (TEM) morphology result is as follows: Figure 1 , the energy spectrum analysis (EDS) results are as follows Figure 2 .
[0060] Comparative Example 1
[0061] This comparative example provides an Au@ZnO nanocomposite material, and its preparation method is as follows:
[0062] (1) Preparation of gold nanoparticle solution: Add 100 mL of water and 125 μL of 100 mmol / L chloroauric acid solution to a three-necked flask. Heat the mixed solution to 145 °C until boiling while stirring vigorously. Quickly add 5 mL of 25 mmol / L sodium citrate solution and heat at 140 °C for 20 minutes. Cool to room temperature and store in a refrigerator at 4 °C.
[0063] (2) Preparation of AuNPs-TGA-PVP solution: Add 100 mL of the gold nanoparticle solution prepared in step (1) and 500 μL of 3 mmol / L ethanolic thioglycolate solution into a flask. Heat the mixed solution to 60°C with vigorous stirring for 2 h. Cool the mixed solution to room temperature and wash it by centrifugation. Mix it evenly with 50 mL of 100 μmol / L aqueous polyvinyl pyrrolidone solution and store it at 4°C.
[0064] (3) Preparation of Au@ZnO solution: Add 50 mL of the AuNPs-TGA-PVP solution prepared in step (2), 1 mL of 250 mmol / L hexamethylenetetramine solution and zinc acetate solution into a flask. Heat the mixed solution at 95 °C for 3 h under vigorous stirring. After cooling to room temperature, centrifuge and wash to obtain the Au@ZnO nanocomposite material. Disperse it back into water and store it in a refrigerator at 4 °C.
[0065] Comparative Example 2
[0066] This comparative example provides an AuPt nanocomposite material, and its preparation method is as follows:
[0067] (1) Preparation of gold nanoparticle solution: Add 100 mL of water and 125 μL of 100 mmol / L chloroauric acid solution to a three-necked flask. Heat the mixed solution to 145 °C until boiling while stirring vigorously. Quickly add 5 mL of 25 mmol / L sodium citrate solution and heat at 140 °C for 20 minutes. Cool to room temperature and store in a refrigerator at 4 °C.
[0068] (2) Preparation of AuNPs-TGA-PVP solution: Add 100 mL of the gold nanoparticle solution prepared in step (1) and 500 μL of 3 mmol / L ethanolic thioglycolate solution into a flask. Heat the mixed solution to 60°C with vigorous stirring for two hours. Cool the mixed solution to room temperature and wash it by centrifugation. Mix it evenly with 50 mL of 100 μmol / L aqueous polyvinyl pyrrolidone solution and store it at 4°C.
[0069] (3) Preparation of AuPt nanocomposites: Take 5 mL of the AuNPs-TGA-PVP solution prepared in step 2 and add it into a flask. Add 25 μL of 100 mmol / L chloroplatinic acid under vigorous stirring to prepare the AuPt nanocomposites. React at room temperature for 12 h and store at 4 °C.
[0070] Comparative Example 3
[0071] This comparative example provides a ZnO / Pt nanocomposite material.
[0072] (1) Preparation of ZnO solution: Add 50 mL of 100 μmol / L polyvinyl pyrrolidone aqueous solution, 1 mL of 250 mmol / L hexamethylenetetramine solution and zinc acetate solution into a flask. Heat the mixed solution at 95 °C for 3 h with vigorous stirring. After cooling to room temperature, wash by centrifugation, disperse back into water, and store in a refrigerator at 4 °C.
[0073] (2) Preparation of ZnO / Pt nanocomposites: Take 5 mL of the ZnO solution prepared in (step 1) and add it into a flask. Add 83 μL of 100 mmol / L chloroplatinic acid under vigorous stirring and react at room temperature for 12 hours to obtain ZnO / Pt nanocomposites, which are then stored in a refrigerator at 4 °C.
[0074] Experimental analysis
[0075] This example tests the oxidase-like activity of Au@ZnO / Pt nanocomposites and other nanocomposites.
[0076] The specific process is:
[0077] In the reaction system, add 10 mmol / L PBS buffer, 0 μmol / L~600 μmol / L 3,3',5,5'-tetramethylbenzidine (TMB) solution, and add 0.2 mmol / L Au@ZnO nanocomposite solution, AuPt nanocomposite solution, ZnO / Pt nanocomposite solution and Au@ZnO / Pt nanocomposite solution respectively, dilute with water to 800 μL, mix well and react immediately, test with UV-visible spectrophotometer, measure the absorbance of the system at the peak near 652 nm, normalize the concentration data of TMB solution and the obtained absorbance data and draw a graph, so as to compare the oxidase-like activity of different nanocomposites.
[0078] Figure 3 This is a comparison chart of the normalized absorbance of Au@ZnO nanocomposite, AuPt nanocomposite, ZnO / Pt nanocomposite and Au@ZnO / Pt nanocomposite after reacting with TMB solutions of different concentrations. It can be found that the absorbance value of the solution after the Au@ZnO / Pt nanocomposite reacts with TMB solution is the largest, indicating that the oxidase-like activity of this nanocomposite is better than that of several other nanocomposites.
[0079] The Au@ZnO / Pt nanocomposite was mixed with TMB and PBS (pH = 4-6) to make a test paper. Tetracycline solutions of different concentrations were added. During the reaction, the zinc ions in the Au@ZnO / Pt nanocomposite reacted with tetracycline to produce specific fluorescence enhancement, converting tetracycline with weak orange fluorescence into tetracycline with strong green fluorescence. The photos after the reaction under ultraviolet light are shown in Figure 4 At the same time, the oxidase-like activity of the Au@ZnO / Pt nanocomposite can catalyze the oxidation of TMB to ox-TMB, producing a blue band, while tetracycline will interact with ox-TMB, hindering this process and causing the color change of the solution. The photo under natural light after the reaction is shown in Figure 5 .
[0080] Figure 6 This is an intuitive enzymatic diagram of Au@ZnO nanocomposite, AuPt nanocomposite, ZnO / Pt nanocomposite and Au@ZnO / Pt nanocomposite. As shown in the figure, the oxidase-like activity of Au@ZnO / Pt nanocomposite is better than that of several other nanocomposites. The oxidase-like activity of Au@ZnO nanocomposite, AuPt nanocomposite and ZnO / Pt nanocomposite is not enough to produce blue bands. Therefore, the color change of subsequent detection of tetracycline is not as obvious as that of Au@ZnO / Pt nanocomposite.
[0081] Application Example 1
[0082] This application example establishes a tetracycline fluorescence analysis method. The specific process is as follows:
[0083] In the reaction system, add 10 mmol / L PBS buffer, 600 μmol / L TMB solution, 0.2 mmol / L Au@ZnO / Pt nanocomposite solution and 0 μmol / L~100 μmol / L tetracycline solution, dilute to 1 mL with water, mix well and react for 1 min, and immediately perform fluorescence test with a fluorescence meter. Under the excitation wavelength of 385 nm, the fluorescence intensity of the system at 525 nm is measured.
[0084] like Figure 7 As shown, Figure 7 -a is the fluorescence emission spectrum of Au@ZnO / Pt nanocomposite in response to different concentrations of tetracycline, Figure 7 -b is the linear relationship between fluorescence intensity and tetracycline concentration. Figure 7 -a It can be seen that in the presence of Au@ZnO / Pt nanocomposites, as the concentration of tetracycline increases, the fluorescence intensity at 525 nm also gradually increases, and there is a quantitative relationship with the concentration of tetracycline; Figure 7 -b shows that the fluorescence intensity and tetracycline concentration show a good linear relationship, and the linear equation of the working curve is y=28.05x+17.18, R 2 =0.9900, the linear detection range was 0.0005 μmol / L~25 μmol / L, and the detection limit was 0.48 nmol / L.
[0085] Application Example 2
[0086] This application example establishes a tetracycline colorimetric analysis method. The specific process is as follows:
[0087] In the reaction system, add 10 mmol / L PBS buffer, 600 μmol / L TMB solution, 0.2 mmol / L Au@ZnO / Pt nanocomposite solution and 0 μmol / L~300 μmol / L tetracycline solution, dilute to 800 μL with water, mix well and react for 1 min, and then immediately test with a UV-visible spectrophotometer. Plot the concentration data of tetracycline and the absorbance data obtained during the detection to obtain the colorimetric working curve of tetracycline.
[0088] like Figure 8 As shown, Figure 8 -a is the UV-visible absorption spectrum of Au@ZnO / Pt nanocomposite in response to different concentrations of tetracycline, Figure 8 -b is the linear relationship between the absorbance at 652 nm and the tetracycline concentration. Figure 8 -a It can be seen that in the presence of Au@ZnO / Pt nanocomposites, as the concentration of tetracycline increases, the absorbance of the absorption spectrum at 652 nm gradually decreases, and there is a quantitative relationship with the concentration of tetracycline; Figure 8 -b It can be seen that the absorbance at 652 nm and the tetracycline concentration show a good linear relationship, and the linear equation of the working curve is y = -0.034x-1.396, R 2 =0.9904, the linear detection range was 0.0005 μmol / L~300 μmol / L, and the detection limit was 0.34 nmol / L.
[0089] Application Example 3
[0090] This application example tests the selectivity of the fluorescence analysis method for tetracycline detection. The specific process is as follows:
[0091] In the reaction system, 10 mmol / L PBS buffer, 600 μmol / L TMB solution and 0.2 mmol / L Au@ZnO / Pt nanocomposite solution were added, and then 25 μmol / L different interfering substance solutions were added, diluted to 1 mL with water, mixed evenly, and reacted for 1 min before fluorescence test was performed immediately. The excitation wavelength was set to 385 nm, and the fluorescence intensity of the system at the peak near 525 nm was measured. Similarly, in the reaction system, 10 mmol / L PBS buffer, 600 μmol / L TMB solution were added, and then 25 μmol / L different interfering substance solutions (potassium ion, sodium ion, ammonium ion, calcium ion, magnesium ion, barium ion, zinc ion, manganese ion, iron ion, chloramphenicol, penicillin G sodium, neomycin sulfate, streptomycin sulfate, kanamycin sulfate, ceftriaxone, amoxicillin, ampicillin, glutamic acid, proline, tyrosine, histidine, histidine, threonine, tryptophan, hydrogen peroxide) were added, diluted to 1 mL with water, mixed evenly, and reacted for 1 min. min later, the fluorescence test was carried out under the same conditions to compare the fluorescence intensity before and after the addition of Au@ZnO / Pt nanocomposite solution.
[0092] The experiment was conducted through the fluorescence response of Au@ZnO / Pt nanocomposites to 45 μmol / L tetracycline and other interfering substances at the same concentration. The test results are as follows: Fig. 9 As shown, it can be found that these interferents have little effect on the detection, indicating that the fluorescence analysis method of the tetracycline detection method has good selectivity.
[0093] Application Example 4
[0094] This application example tests the selectivity of the colorimetric method for tetracycline detection. The specific process is as follows:
[0095] In the reaction system, 10 mmol / L PBS buffer, 600 μmol / L TMB solution and 0.2 mmol / L Au@ZnO / Pt nanocomposite solution were added, and then 100 μmol / L different interfering substance solutions were added, diluted to 800 μL with water, mixed evenly, and tested immediately with a UV-visible spectrophotometer after 1 min of reaction to measure the absorbance of the system at the peak near 652 nm; similarly, in the reaction system, 10 mmol / L PBS buffer, 600 μmol / L TMB solution were added, and then 100 μmol / L different interfering substance solutions (same as Application Example 3) were added, diluted to 800 μL with water, mixed evenly, and tested with a UV-visible spectrophotometer under the same conditions after 1 min of reaction to compare the absorbance before and after the addition of the Au@ZnO / Pt nanocomposite solution.
[0096] The experiment obtained the following detection results through the absorbance data of Au@ZnO / Pt nanocomposites for 100 μmol / L tetracycline and other interfering substances at the same concentration. Fig.10 As shown, it can be found that these interferents have little effect on the detection, indicating that the colorimetric analysis method of tetracycline detection has good selectivity.
[0097] Application Example 5
[0098] This application example investigates the detection of tetracycline in actual samples and the recovery rate of the detection method. The specific process is as follows:
[0099] In the reaction system, 10 mmol / L PBS buffer, 600 μmol / L TMB solution and 0.2 mmol / L Au@ZnO / Pt nanocomposite solution were added, and then 1 mL of real tetracycline sample solution was added, diluted to 2 mL with ultrapure water, and mixed evenly. The solution after mixing and reacting for 1 min was used for fluorescence test and UV-visible absorption test respectively. According to the measured fluorescence intensity and absorbance and the corresponding working curve, the ratio percentage between the concentration value B determined by this method and the actual sample concentration A was calculated, and the recovery rate of this method was obtained as (A / B) × 100%.
[0100] The results are shown in Table 1 below:
[0101] Table 1 Content and recovery rate of tetracycline in actual samples (n=5)
[0102]
[0103] Result analysis: From the above table, we can see that the recovery rates of the two detection methods are between 80% and 120%, which has good practical application value.
[0104] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a nanocomposite material, characterized in that: The nanocomposite material is a core-shell structure, the shell layer is zinc oxide, the core is gold nanoparticles, and the shell layer is loaded with platinum nanoparticles; the preparation method of the nanocomposite material comprises the following steps: S1, adding a thiol small molecule to the gold nanoparticle solution to react and obtain a reactant 1; S2, reacting the reactant 1 with a zinc source and hexamethylenetetramine to obtain a reactant 2; S3, the reactant 2 reacts with a platinum source to obtain the nanocomposite material.
2. The method for preparing the nanocomposite material according to claim 1, characterized in that: The molar ratio of zinc oxide, gold nanoparticles and platinum nanoparticles is 10:(0.5-2):(0.5-2).
3. The method for preparing the nanocomposite material according to claim 1, characterized in that: In step S1, the gold nanoparticles are prepared by the following steps: a gold source reacts with a reducing agent to prepare the gold nanoparticles; And / or, the thiol small molecule is selected from one or more of thioglycolic acid, thioglycolate, mercaptoethanol, thioethanol salt, mercaptoethanesulfonic acid and mercaptoethanesulfonate; And / or, step S1 further comprises: adding reactant 1 to a solution containing a stabilizer, wherein the stabilizer is selected from one or more of PVP, PVA, Tween-80, and sodium dodecylbenzene sulfonate.
4. The method for preparing the nanocomposite material according to claim 1, characterized in that: In step S2, the zinc source is selected from one or more of zinc acetate, zinc nitrate, zinc sulfate and zinc chloride; And / or, in step S3, the platinum source is selected from one or more of sodium chloroplatinite, potassium chloroplatinite, ammonium chloroplatinite, chloroplatinic acid, and sodium chloroplatinate.
5. The method for preparing the nanocomposite material according to claim 1, characterized in that: In step S1, the reaction temperature is 50-70°C and the reaction time is 1-3 h.
6. Use of the nanocomposite material prepared by the preparation method according to any one of claims 1 to 5 in detecting tetracycline antibiotics.
7. The use according to claim 6, characterized in that The nanocomposite material is used in preparing a fluorescent probe or a test strip for detecting tetracycline antibiotics.
8. A method for detecting the concentration of tetracycline antibiotics, characterized in that: The steps include: 1) Mixing the nanocomposite material prepared by the preparation method according to any one of claims 1 to 5, 3,3',5,5'-tetramethylbenzidine and a tetracycline antibiotic standard solution to obtain a mixed solution, detecting the fluorescence intensity and / or ultraviolet absorbance of the mixed solution, and establishing a relevant working curve; 2) The method in step 1) is used to detect the fluorescence intensity and / or ultraviolet light absorbance of the test solution containing tetracycline antibiotics, and the concentration of the tetracycline antibiotics in the test solution is calculated.
9. The method for detecting tetracycline antibiotics according to claim 8, characterized in that: The detection range of the fluorescence intensity is 400-650 nm; And / or, the detection range of the ultraviolet absorbance is 200-800 nm.
Citation Information
Patent Citations
Gold / platinum bimetal nanocluster fluorescence probe based on polyethyleneimine protection, and application of fluorescence probe in aureomycin detection
CN107118758A
Method for making a film of uniformly arranged core-shell nanoparticles on a substrate
US20140138352A1